Problematika Anak Angkat Dalam Perspektif Hukum Islam - Erva Dyana Puri; Emmi Saidatul Khairi; Fathiyah Hanin Munthe; Geby Septia Handayani (Tabayyun : Journal Of Islamic Studies, 2024)
Regarding the concept of child adoption within the scope of Islamic law, the aim is to understand the concept of child adoption within the scope of Islamic law for the implementation of the child adoption process in religious courts. The concept of adopting a child in Islamic law does not mean being an absolute biological child, but only being allowed to care for and care for it with the aim of treating the child in terms of love, providing support, education or services for all needs, not treating them as a biological child (nasab). Adoption of a child based on Islamic law is the adoption of a child that is based on the Koran and Sunnah as well as the results of ijtihad in force in Indonesia which is formulated in various products of Islamic legal thought, both in the form of fiqh, fatwa, court decisions, and statutory regulations including them. compilation of Islamic law or KHI.